Sistem Kendali dan Monitoring Kecepatan Motor Servo Berbasis Human Machine Interface - Fahrul Dames; Doni Tri Putra Yanto (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
The servo motor control and monitoring system based on the human machine interface is a system that can control and monitor the speed of the servo motor. Servo motors can be controlled and monitored because of the mutual communication between the motor driver and the encoder that translates and controls the servo motor. The motor driver works on the command of a programmable logic controller that has been programmed with the help of a computer. For control and monitoring, the human machine interface is used as a tool that can interact with the user as a controller as well as monitoring the speed and position of the servo motor. The hardware used is the SIEMENS SIMATIC 1215C DC/DC/DC programmable logic controller, SIMATIC BASIC COMFORT human machine interface, SINAMICS V90 motor driver and SIMOTICS S-1FL6 servo motor. TIA PORTAL and V-Assistant software are used for programming and parameter setting of each system hardware.